PENGARUH PENGAWASAN MELEKAT TERHADAP DISIPLIN KERJA PEGAWAI BIDANG PERTANAHAN PADA DINAS PERUMAHAN, KAWASAN PERMUKIMAN DAN PERTANAHAN KABUPATEN SUMEDANG - irma hermayanty; Ika Rismawati; Melly Martiani; Yusi Rosdamayanti; Rinrin Ristiani; Sarah Talis Ramadiah (JRPA - Journal of Regional Public Administration, 2022)
The purpose of the research conducted was to find out the Influence of Inherent Supervision on Employee Work Discipline in the Land Sector in the Housing Office, Settlement And Land Area of Sumedang Regency and to know how much influence between inherent supervision and employee work discipline in the Housing Office, Residential Area and Land Of Sumedang Regency. The method used in this research is a quantitative research method that is used in research based on the philosophy of positivism with the aim of testing established hypotheses. In this study, researchers used an inferential descriptive data analysis technique that describes or describes data that has been collected as is by making conclusions that apply to the public. The technique used in this study is a saturated sampling technique, with a population of 66 people, and a sample of 18 people due to variables taken by researchers, namelyemployee discipline variables that focus on one of the fields, namely in the field of Land. Based on the results of the research, the implementation of Inherent Supervision conducted by the Housing Office, Settlement And Land Area of Sumedang Regency has reached 84.32% and the figure is categorized very well, as well as the level of Employee Work Discipline in the Housing Office, Residential Area and Land of Sumedang Regency. It reached 81.0535% and the figure is categorized as good. The relationship of Supervision Attached to Employee Work Discipline in the Housing Office, Settlement and Land Area of Sumedang Regency with a correlation coefficient value of 0.680 is in a strong category. Next ????â„Ž???????????????????? Bigger than ???????????????????????? or 0.002 < 0.05. From the Determination Coefficient Analysis it is known that the inherent supervisory variables have an influence on the discipline of work The remaining 46% by 54% is influenced by factors other than supervision.